MUC1 intracellular bioactivation mediates lung fibrosis. Issue 2 (4th December 2019) - Milara, Javier; Ballester, Beatriz; Montero, Paula; Escriva, Juan; Artigues, Enrique; Alós, Manuel; Pastor-Clerigues, Alfonso; Morcillo, Esteban; Cortijo, Julio
Abstract : Background: Serum KL6/mucin 1 (MUC1) has been identified as a potential biomarker in idiopathic pulmonary fibrosis (IPF), but the role of MUC1 intracellular bioactivation in IPF is unknown. Objective: To characterise MUC1 intracellular bioactivation in IPF. Methods and results: The expression and phosphorylation of Thr 41 and Tyr 46 on the intracellular MUC1-cytoplasmic tail (CT) was increased in patients with IPF (n=22) compared with healthy subjects (n=21) and localised to fibroblasts and hyperplastic alveolar type II cells. Transforming growth factor (TGF)-β1 phosphorylated SMAD3 and thereby increased the phosphorylation of MUC1-CT Thr 41 and Tyr 46 in lung fibroblasts and alveolar type II cells, activating β-catenin to form a phospho-Smad3/MUC1-CT and MUC1-CT/β-catenin nuclear complex. This nuclear complex promoted alveolar epithelial type II and fibroblast to myofibroblast transitions, as well as cell senescence and fibroblast proliferation. The inhibition of MUC1-CT nuclear translocation using the inhibitor, GO-201 or silencing MUC1 by siRNA, reduced myofibroblast transition, senescence and proliferation in vitro. Bleomycin-induced lung fibrosis was reduced in mice treated with GO-201 and in MUC1-knockout mice. The profibrotic lectin, galectin-3, directly activated MUC1-CT and served as a bridge between the TGF-β receptor and the MUC1-C domain, indicating TGF-β1-dependent and TGF-β1-independent intracellular bioactivation of MUC1. Conclusions: MUC1 intracellular bioactivation is enhanced in IPF and promotes fibrotic processes that could represent potential druggable targets for IPF.